Weed Biomass and Productivity of Okra (Abelmoschus esculentus (L) Moench) As Influenced by Spacing and Pendimethalin – Based Weed Management - Emmanuel, Imoloame Oyamedan (Journal of Agricultural Sciences (Belgrade), 2019)
Field trials were conducted at the Teaching and Research Farm of the Kwara State University, Malete, Nigeria, to determine the effect of plant spacing and weed control methods on weed infestation, growth and yield of okra during the 2016 and 2017 cropping seasons. The experiment consisted of twelve treatments comprising six weed control methods and two plant spacing. The method of weed control  consisted of pre-emergence application of pendimethalin at 1.0 kg a.i.ha-1, pendimethalin at 2.0 kg a.i.ha-1, pendimathalin at 1.0 kg a.i.ha-1 + one supplementary hoe-weeding (SHW) at 6 weeks after sowing (WAS), two hoe  weeding at 3 and 6 weeks after sowing (WAS), weeding at 4 and 8 weeks after sowing (WAS) and a weedy check. The plant spacing were 60x30cm and 60x50cm. These treatments were laid out in randomized complete block design (RCBD) with split plot arrangement and replicated three times.  Weed control and plant spacing treatments were allocated to the main and sub plots respectively. Results showed that plant spacing of 60cm x30cm minimized weed infestation and resulted in higher total number of pods/plot and okra fresh weight, while plots treated with pendimethalin at 1.0 kg a.i./ha + one supplementary hoe weeding at 6 WAS minimized weed infestation, had the highest total number of pods and yield of okra. This combination also promoted higher economic returns.